AFM-based indentation method for measuring the relaxation property of living cells. (9th June 2021) - Sheng, Jun-Yuan; Mo, Chi; Li, Guo-Yang; Zhao, Hu-Cheng; Cao, Yanping; Feng, Xi-Qiao
Abstract: Probing the mechanical properties of cells is critical for understanding their deformation behaviors and biological functions. Although some methods have been proposed to characterize the elastic properties of cells, it is still difficult to measure their time-dependent properties. This paper investigates the use of atomic force microscope (AFM) to determine the reduced relaxation modulus of cells. In principle, AFM is hard to perform an indentation relaxation test that requires a constant indenter displacement during load relaxation, whereas the real AFM indenter displacement usually varies with time during relaxation due to the relatively small bending stiffness of its cantilever. We investigate this issue through a combined theoretical, computational, and experimental effort. A protocol relying on the choice of appropriate cantilever bending stiffness is proposed to perform an AFM-based indentation relaxation test of cells, which enables the measurement of reduced relaxation modulus with high accuracy. This protocol is first validated by performing nanoindentation relaxation tests on a soft material and by comparing the results with those from independent measurements. Then indentation tests of cartilage cells are conducted to demonstrate this method in determining time-dependent properties of living cells. Finally, the change in the viscoelasticity of MCF-7 cells under hyperthermia is investigated.